(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
The article aims to improve the production of organic and environmentally pure environmentally friendly products in the production of quality food in the country’s agriculture and the supply of the population. Proposals and recommendations are also made to further improve the introduction of international stadarts of the International Global Good Agriculture Programm (G.A.P) in the export of organic and environmentally friendly products.